Coach-led preventive training program in youth soccer players improves movement technique. Issue 9 (September 2017) - Pryor, J. Luke; Root, Hayley J.; Vandermark, Lesley W.; Pryor, Riana R.; Martinez, Jessica C.; Trojian, Thomas H.; Denegar, Craig R.; DiStefano, Lindsay J.
Abstract: Long-term implementation of preventive training programs (PTP) in youth sport requires coach involvement. However, the optimal training of coaches to effectively implement a PTP remains unknown. It is also unknown if the benefits of PTP can be enhanced with multiple sport seasons of exposure. Objectives: To evaluate the influence of prior PTP exposure on movement technique in youth soccer players after completing a coach-led PTP. Design: Cluster-randomized controlled trial. Methods: Twelve youth soccer teams (n = 89; age range 8–14 years) were divided into groups with (Experience (EXP); 6 teams [n = 18 females, n = 25 males]) and without (Novice (NOV); 6 teams [n = 30 females, n = 16 males]) previous professional-led PTP experience. The coaches and players of the EXP teams were exposed to an eight-week professional-led PTP before the coach-led PTP. EXP and NOV coaches attended the educational workshop prior to implementing the coach-led PTP. The Landing Error Scoring System (LESS) was used to evaluate movement technique. Results: Both groups improved LESS scores over time (mean difference ± SD [post-pre] = −0.8 ± 0.2, 95%CI [−1.2, −0.4], p = 0.0001). Of the 64 participants classified as high risk for injury (LESS ≥5) prior to PTP implementation, a greater proportion of EXP (n = 14) compared to NOV (n = 7) participants changed risk classification from high to low (LESSΔ ≥ 1 and LESS <5; p = 0.03). Conclusions: Our PTP enhanced movement technique regardless of PTP experience, but the benefits of the PTP impacted a proportionally greater number of players with previous PTP experience supporting continued PTP implementation. Coaches effectively implemented an exercise-based PTP after attending a training workshop regardless of previous PTP experience.